2023
DOI: 10.1123/japa.2022-0098
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Physical Activity Are Important in Managing Anxiety in Older Adults: A Systematic Review and Meta-Analysis

Abstract: Physical activity (PA) is a known approach for managing anxiety symptoms in older adults. This systematic review and meta-analysis address the benefits of PA and its dimensions (frequency, session time, type, and intervention period) on anxiety symptoms in older adults aged 65 years and above. Searches covered eight databases reporting eight randomized controlled trials (RCTs) and five non-RCTs. Meta-analysis of RCTs (standardized mean difference = −0.41; 95% confidence interval [−0.58, −0.24]; p < .00001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…However, in the present systematic review, we were unable to identify a meta-analysis on anxiety and exercise that had been conducted with older adults in CS. A recent meta-analysis that included studies with a truly heterogeneous population (community-dwelling and those in CS) showed that PA diminished anxiety symptoms [ 53 ]. Although this meta-analysis was not included in our systematic review, it is noteworthy as it included community-dwelling participants and it demonstrates that exercise may affect anxiety in this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present systematic review, we were unable to identify a meta-analysis on anxiety and exercise that had been conducted with older adults in CS. A recent meta-analysis that included studies with a truly heterogeneous population (community-dwelling and those in CS) showed that PA diminished anxiety symptoms [ 53 ]. Although this meta-analysis was not included in our systematic review, it is noteworthy as it included community-dwelling participants and it demonstrates that exercise may affect anxiety in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of depression were classified as follows: normal (0-4), mild (5-9), moderate (10-14) and severe. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] The GAD-7 comprised 7 items using a 4-point Likert scale ranging from 0 (not at all) to 3 (nearly every day), with a total score between 0 and 21. The levels of anxiety were classified as follows: normal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14) and severe.…”
Section: Depression and Anxiety Assessmentmentioning
confidence: 99%
“…[12][13][14][15] Several systematic reviews and meta-analyses have strengthened the effectiveness of physical activity or daily exercise in managing depression or anxiety. [16][17][18] However, from the perspective of aetiological prevention, the association of physical activity with anxiety did not reach a conclusive result; some studies have found that physical activity or exercise can reduce the incidence of anxiety, 19 while others reported no association. 20 21 Gender was found to play a significant role in influencing anxiety and depression levels, and a lack of exercise might exacerbate the symptoms in both genders when compared with physically active individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a decline in physical function is commonly observed with ageing, increasing older adults' vulnerability to falling, frailty, rising healthcare costs and premature death (25)(26)(27). While these challenges can have profound negative impacts on older adults, research has demonstrated that PA can counterbalance these challenges and positively in uence healthy ageing by improving cortisol and/or DHEA(S) levels (28), anxiety and depression (29), muscle mass, strength, and thus physical function, frailty, and quality of life (30)(31)(32)(33)(34) Therefore, PA interventions are a viable approach to mitigating the adverse effects of ageing on the endocrine system, psychological wellbeing, and physical function in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the evidence for the effects of digital PA resources on steroid hormones in older adults is scarce. For example, several studies have noted a lack of quality evidence for the impact of PA interventions in care home residents on anxiety symptoms, cortisol and DHEA(S) (28,29,43). In addition, there is evidence that conducting PA in a group can enhance the effects of the intervention by enhancing social connectedness and reducing loneliness (34,44,45).…”
Section: Introductionmentioning
confidence: 99%